Pengaruh Tradisi Mappadekko Pada Hasil Panen Masyarakat Di Desa Walenreng Kabupaten Bone - Muh. Farhi; Ais Magfirah Maulani; Nur Fauziah Ikhwan; Ahmad Kurniawan; Sendi Safitri; Kristiawati Kristiawati (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
There is a perception from the community towards the Mappadekko tradition which is believed to have an influence on the harvests of the Walenreng Village farming community. The problems in the research are considered important to be carried out in order to find answers to the beliefs held by conducting a study regarding